Straightforward synthesis of novel 1-(2'-α-O-D-glucopyranosyl ethyl) 2-arylbenzimidazoles - Arumugam, Natarajan; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Osman, Hasnah (MDPI, 2012)
A series of novel 1-(2'-α-O-D-glucopyranosyl ethyl) 2-arylbenzimidazoles has been prepared via one-pot glycosylation of ethyl-1-(2'-hydroxyethyl)-2-arylbenzimidazole-5-carboxylate derivatives. Synthesis of the 2-arylbenzimidazole aglycones from 4-fluoro-3-nitrobenzoic acid was accomplished in four high-yielding steps. The reduction and cyclocondensation steps for the aglycone synthesis proceeded efficiently under microwave irradiation to afford the appropriate benzimidazoles in excellent yields within 2-3 min. Glycosylation of the hydroxyethyl aglycones with the perbenzylated 1-hydroxy- glucopyranose, pretreated with the Appel-Lee reagent, followed by catalytic hydrogenolysis delivered the desired 1-(2'-α-O-D-glucopyranosyl ethyl) 2-aryl-benzimidazoles in a simple and straightforward manner.